Helicobacter pylori and non‐alcoholic fatty liver disease: A new enigma?. Issue 6 (23rd September 2018) - Abdel‐Razik, Ahmed; Mousa, Nasser; Shabana, Walaa; Refaey, Mohamed; Elhelaly, Rania; Elzehery, Rasha; Abdelsalam, Mostafa; Elgamal, Ayman; Nassar, Mervat R.; Abu El‐Soud, Atef; Seif, Ahmed S.; Tawfik, Ahmed M.; et al.
Abstract: Background and Aim: The relationship between Helicobacter pylori ( H. pylori ) and nonalcoholic fatty liver disease (NAFLD) is a matter of debate. We achieved this prospective work to study whether H. pylori infection is a risk factor for NAFLD. Methods: A cohort multicenter pilot study of 369 adults without NAFLD at baseline was followed up for 2 years. Serum leptin, insulin, tumor necrosis factor‐α, adiponectin, and interleukin‐6 were measured using an enzyme‐linked immunosorbent assay (ELISA). Homeostasis model assessment of insulin resistance (HOMA‐IR) and leptin/adiponectin ratio (LAR) were calculated. Fecal H. pylori antigen was measured by ELISA. A total of 127 participants with H. pylori positive were treated and then followed up for 3 months. Results: Helicobacter pylori ‐positive patients (46.3%) were associated with an increase in IR, proinflammatory cytokines, C‐reactive protein (CRP), LAR, NAFLD‐liver fat score (NAFLD‐LFS), and hepatic steatosis index (HSI) (all P < 0.01). Multivariate analysis of NAFLD according to HSI and NAFLD‐LFS reported that presence of H. pylori, LAR, CRP, IL‐6, smoking, and age (all P < 0.01) were independent risk factors for the presence of NAFLD. Multiple models adjusted for potential mediators or confounders such as metabolic, inflammatory, and biochemical factors were constructed. After therapy of H. pylori infection, there was a significant reduction in lipogenic profile, IR, leptin, LAR, CRP, proinflammatory cytokines, HSI, and NAFLD‐LFS, as well as, increasing HDL. Conclusion: Helicobacter pylori infection was related to an increased risk of NAFLD development, through increased markers of IR, inflammatory mediators, and lipid metabolism. Moreover, its eradication can recover these NAFLD risk factors.